Dissecting the rural Indian women’s knowledge, attitude and practice about infertility - U., Ashwini Nayak; G., Ramakrishnan K.; N., Venkateshwar K.; M., Vijayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of present study was to evaluate the knowledge, attitude and practice of rural women regarding infertility. Methods: A field tested semi-structured questionnaire was administered to 100 rural women in Kaiwara village, Karnataka, India to study their knowledge, attitude and practice regarding infertility. Results: Majority (84%) did not know the reason for infertility. 7% felt that the cause of infertility was due to problems with eggs, 6% felt it to be tubal factors and only 3% felt it to be due to male factor. Conclusions: The findings of this study highlight the importance of spreading the awareness and inculcating the right attitude and approach to infertility.